Development of a fully human glioblastoma-in-brain-spheroid model for accelerated translational research - Horschitz, Sandra; Jabali, Ammar; Heuer, Sophie; Zillich, Eric; Zillich, Lea; Hoffmann, Dirk C.; Kumar, Akshaya Senthil; Hausmann, David; Azorin, Daniel Dominguez; Hai, Ling; Wick, Wolfgang; Winkler, Frank; et al. (Journal of advanced research, 2026)
Introduction - Glioblastoma (GBM) progression and therapeutic resistance are significantly influenced by complex interactions between tumor cells and the brain microenvironment, particularly neurons. However, studying these interactions in physiologically relevant conditions has remained challenging due to limitations in existing model systems. - Objectives - Here, we present hGliCS (human glioma-cortical spheroid), a novel fully human brain tumor model that overcomes key limitations of current approaches by combining patient-derived GBM cells with mature human cortical neurons derived from induced pluripotent stem cells. - Results - We demonstrate that GBM cells in hGliCS develop three critical hallmark features observed in patients: (i) formation of tumor microtubes enabling intercellular communication, (ii) establishment of neuron-glioma synapses, and (iii) development of an interconnected network with coordinated calcium signaling. Single-cell RNA sequencing reveals that tumor cells in hGliCS exhibit cellular heterogeneity and transcriptional profiles remarkably similar to those observed in mouse xenografts, including activation of key oncogenic pathways and neuronal-like features. Notably, while GBM cells showed substantial transcriptional adaptation to the neural environment, neurons maintained their core identity with only subtle alterations in glutamate signaling and structural gene expression. We validate hGliCS as a drug screening platform by demonstrating resistance patterns to standard chemotherapy and radiation similar to clinical observations. Furthermore, we show the model’s utility in testing standard and novel therapeutic compounds targeting cell proliferation and tumor-specific neurobiological features, respectively. - Conclusion - This physiologically relevant human model system provides new opportunities for studying GBM biology and tumor-neuron interactions in a controlled environment. By bridging the gap between simplified in vitro systems and complex in vivo models, hGliCS represents a promising platform for therapeutic development and personalized medicine approaches in GBM treatment.